Measuring Performance in Interagency Collaboration: FEMA Corps. Issue 3 (15th June 2017) - Ward, Kevin D.; Epstein, Diana; Varda, Danielle; Lane, Barbara
Abstract : The U.S. Office of Management and Budget and other federal government stakeholders have been encouraging federal agencies to partner and collaborate to solve increasingly complex public problems. However, developing and implementing performance measures in collaborative or partnership arrangements adds complexity to an already complex process. In the case of one interagency partnership, the FEMA Corps, implementing a mechanism to collect and report data demonstrating accomplishments has presented both challenges and opportunities. Through this research, the practitioner‐scholar research team uses the partnership between FEMA and a program of the Corporation for National and Community Service (CNCS) as a case study demonstrating what it takes for two federal agencies to successfully collaborate on data collection and reporting. Despite the challenge, findings demonstrate that the process of developing and implementing joint performance measures may facilitate important conversations relating to the mission, vision, and goals of the partnership.